Astrocyte calcium signalling orchestrates neuronal synchronization in organotypic hippocampal slices. (19th May 2014) - Sasaki, Takuya; Ishikawa, Tomoe; Abe, Reimi; Nakayama, Ryota; Asada, Akiko; Matsuki, Norio; Ikegaya, Yuji
Abstract : Key points: In the brain, astrocytes detect neuronal activity and regulate neuronal excitability and synaptic transmission. Recent studies show that calcium elevations that are localized within astrocyte processes upregulate endogenous neurotransmission at nearby synapses. We demonstrated that at the network level calcium buffering in astrocytes caused a significant reduction in the correlated activity of neurons in cultured hippocampal slices. In contrast, the uncaging of calcium in astrocytes triggered synchronized activity in neuronal populations. This study provides experimental support for the functional relevance of astrocyte signalling to the maintenance of collective neuronal dynamics. Abstract: Astrocytes are thought to detect neuronal activity in the form of intracellular calcium elevations; thereby, astrocytes can regulate neuronal excitability and synaptic transmission. Little is known, however, about how the astrocyte calcium signal regulates the activity of neuronal populations. In this study, we addressed this issue using functional multineuron calcium imaging in hippocampal slice cultures. Under normal conditions, CA3 neuronal networks exhibited temporally correlated activity patterns, occasionally generating large synchronization among a subset of cells. The synchronized neuronal activity was correlated with astrocyte calcium events. Calcium buffering by an intracellular injection of a calcium chelator into multiple astrocytes reduced the synaptic strength of unitary transmission between pairs of surrounding pyramidal cells and caused desynchronization of the neuronal networks. Uncaging the calcium in the astrocytes increased the frequency of neuronal synchronization. These data suggest an essential role of the astrocyte calcium signal in the maintenance of basal neuronal function at the circuit level.